Multipurpose jacket with thermal technology / Anis Fathiah Fazer ... [et al.] - Fazer, Anis Fathiah; Mohd Sabri, Nur Najihah; Wahir, Izzah Amirah; Suhaimi, Nur Elia Farhana; Ramli, Elly Elyanna; Mohd Zaid, Ummi Liyana; Raja Fuad, Raja Noor Shareena (2023)
A multipurpose jacket with heating technology, tailored specifically for motorcyclists who rely on their bikes as their primary mode of transportation, is currently in development. This innovative product is geared towards a range of motorcycle riders, including those who work as Food Panda and Grab Food delivery riders. However, it also has a wider target audience, making it suitable for those living in high-altitude regions with cold temperatures and even flood victims. The jacket boasts an advanced heating element that can be activated with technology. Its Multi- Zone Heating application allows wearers to program their desired temperature easily. Additionally, incorporating smart fabric technology ensures that the jacket is a functional and fashionable outdoor garment that can monitor external temperature and weather conditions. Furthermore, this multipurpose jacket with heating technology aims to enhance the integration of technology in daily life, in line with the rapid development of technology around the globe. Moreover, it seeks to comfort those victims of natural disasters by providing warmth to its users. This product is expected to stand out in the market due to its unique features, which provide consumers with the comfort and convenience they need daily, thanks to its user-friendly design.